الأبعاد التربوية الأخلاقية في التشبيهات القرآنية: سورة الرحمن أنموذجا - العزاوى، محمد عباس عبود (مؤسسة كنوز الحكمة للنشر والتوزيع, 2022)
الحمد لله رب العالمين، الأبعاد التربوية الأخلاقية في التشبيهات القرآنية سورة الرحمن أنموذجا بهدف من هذا البحث بيان جانب من التربية الأخلاقية في القرآن الكريم مع الإعجاز القرآني وذلك من خلال دراسة التشبيهات القرآنية، ومعرفة الأبعاد التربوية المؤثرة على منظومة السلوك الإنساني، من خلال جمع الآيات المشتملة على التشبيهات القرآنية في سورة الرحمن من خلال نطاق حدود البحث، حيث تناولها استنتاج الأبعاد التربوية الأخلاقية ومدلولاتها الإيمانية، في محاولة لأثراء الساحة التربوية القرآنية. حيث مشكلة البحث تفتقر إلى لغة المفسرين والذين تحدثوا عن التشبيهات القرآنية، الهدف البحث الرئيس الذي يسعى لتحقيقه هو استنتاج الأبعاد التربوية الأخلاقية والمؤثرة على منظومة السلوك الإنساني، التي تتضمنها التشبيهات القرآنية في سورة الرحمن أنموذجا: قد اعتمد في هذا البحث المنهج الاستقرائي بتتبع الآيات القرآنية على التشبيهات وجمعها، ثم تحليها بذكر عناصر التشبيه والمعنى الإجمالي للآية والإشارة إلى البعد التربوي الأخلاقي من خلال المنهج التحليلي. قد أسفر هذا البحث مجموعة من النتائج أهمها: أن القرآن الكريم في مجمله يحمل قيما تربوية أخلاقية تطهر النفس وتزكيها، أهم التوصيات البحث إعادة تقديم وطرح مادة التشبيهات القرآنية للنشء من خلال بعض الوسائل التعليمية الحديثة والمعتمدة على الصورة الحركة. بهدف البحث هو غرس القيم وتعزيز مكارم الأخلاق، ومن ذلك أسلوب التشبيه الذي يعتبر من الأساليب الفريدة في التربية الأخلاقية في القرآن الكريم وتعزيز القيم والمفاهيم العامة بأسلوب بياني راقي. Praise be to God, Lord of the Worlds, Ethical Educational Dimensions in Qur’anic Similes Surat Al-Rahman as a model The aim of this research is to show an aspect of moral education in the Holy Qur’an with the Qur’anic miracle, through the study of Qur’anic analogies, and knowledge of the educational dimensions affecting the system of human behavior, by collecting verses that include: Quranic similes in Surat Al-Rahman through the scope of the research limits. Where it dealt with the conclusion of the moral educational dimensions and their faith implications, in an attempt to enrich the Quranic educational arena. Where the research problem lacks the language of the commentators and those who talked about Quranic similes, the main research goal that it seeks to achieve is to deduce the ethical and educational dimensions affecting the human behavior system, which are included in the Quranic analogies in Surat Al-Rahman as a model: In this research, the inductive approach was adopted by following the Qur’anic verses on similes and collecting them, then analyzing them by mentioning the elements of simile and the overall meaning of the verse and referring to the moral educational dimension through the analytical method. This research has resulted in a set of results, the most important of which are: that the Holy Qur’an in its entirety carries moral educational values 'purify and purify the soul. The aim of the research is to instill values and promote noble morals, including the simile method, which is considered one of the unique methods of moral education in the Holy Qur’an and the promotion of general values and concepts in a sophisticated graphic style.
Keywords: الإعجاز القرآني -- التربية الأخلاقية -- تفسير القرآن الكريم -- القيم الإسلامية